The MATRICS Consensus Cognitive Battery: Psychometric Properties of the Chinese Version in Young Patients With Major Depression Disorder - Liang, Sixiang; Xing, Xiaomeng; Wang, Mingwan; Wei, Dan; Tian, Tengfei; Liu, Jun; Sha, Sha (Frontiers in Psychiatry, 2021)
Background: Young patients with major depressive disorder are also associated with cognitive deficits. The development of an accurate and effective battery to measure cognitive impairment in Y-MDD is necessary for both research and clinical practice. This study was designed to test the psychometric properties of the MATRICS Consensus Cognitive Battery (MCCB) in Y-MDD. Method: Fifty Y-MDD patients, thirty-eight euthymic young patients with bipolar disorder (Y-BD) and fifty-one healthy teenagers were recruited. The MCCB and the Montreal Cognitive Assessment (MoCA) were administered to assess cognitive impairment at baseline. The MCCB was also assessed two weeks later in Y-MDD patients. All subjects were between the ages of 13 and 24 years. Result: In the current study, cognitive impairment was greater in young BD patients than in Y-MDD patients in some domains. The MCCB has good internal consistency and reliability in Y-MDD patients. The Pearson correlation coefficients for retest reliability were good. Our findings also revealed an acceptable correlation between the MCCB and the MoCA, indicating good concurrent validity of the MCCB. Furthermore, exploratory factor analysis of the MCCB in Y-MDD patients revealed five domains with acceptable internal structures. Conclusion: The MCCB has acceptable psychometric properties and is a sensitive battery of cognitive impairment in Y-MDD patients. In the future, additional studies need to be carried out with larger samples while controlling for the use of psychotropic medications and antidepressants to validate the findings of the present study.